Performance in propitiatory reconciliation among the Nandi community - Anthony Biwott; Collins Kenga Mumbo; Robert Oduori (Tydskrif vir Letterkunde, 2023)
Propitiation is part of what it means to be human. Traditionally, propitiation has been studied from a broad sociocultural perspective with little consideration of the performance processes at play. Among the Nandi community in Kenya, propitiatory offering reconciliation forms the core of restoration of inter-communities relationships. It defines and enriches their culture, but what is propitiatory offering reconciliation? How is it performed? Are there any steps followed in its execution? Is there a specific place of performance? In this article we provide a framework to understand the Nandi propitiatory reconciliation through a literary perspective. We expound on the steps followed: investigation, interrogation, and cleansing, and the three features of performance: that is, place of performance, actions and signs, formulaic expression, costumes, and audience. The data collection took place in Kabiyet and Kipkaren Wards in Nandi county and was collected through participatory observation, interviews, and questionnaires. The sample population was 30 adults between the ages of 45–90 years who were selected using purposive and snowball sampling techniques. The data collected on performance in propitiatory reconciliation rites was analysed by use of functionalism theory as expounded by Foley. We found that the stages of propitiatory reconciliation must be religiously adhered to for its effectiveness and that the success of its performance heavily depends on the participation of its performers and audience. This article also brings out performance in form of particular acts, singing, and chanting.